Musical psychology. Syllabus - Hryhorieva, Victoriia (Berdiansk State Pedagogical University, 2025)
The purpose of teaching the educational discipline "Musical Psychology" is to form a comprehensively developed personality of a master's student-musician, to prepare a competitive specialist for pedagogical management of the process of forming the musical culture of students of higher educational institutions; formation of knowledge about research methods and directions of music psychology; expressive possibilities of musical art, peculiarities of its perception and cognitive processes in the activity of a musician; basics of musical and creative activity; equipping applicants with the knowledge and skills necessary for further musical and pedagogical activities within the framework of European integration processes; the development of musical perception and thinking as a psychological tool for human communication with art.
Keywords: musical psychology; musical activity; musical perception; musical abilities; associative thinking; performing activity; pop excitement